The Impact Of Using Series Of Picture In Constructing Narrative Text For The Students At Ninth Grade At SMPN 2 Geger Madiun In Contextual Teaching And Learning Process Academic Year 2013 - 2014 - Purnomo, Prapto; , Agus Wijayanto, Ph.D; , Dra. Siti Zuhriyah Ariatmi, M. Hum (2014)
The tendency of using series of pictures in constructing narrative text for students leads to a questions whether using series of pictures in constructing narrative text have any significant affect with the student's achievement. This study was intended to know whether teaching writing using series of pictures at the students in teaching and learning process really affect the student's achievements in their examination. There were two groups of the third grade of junior high school students adopted from SMPN 2 Geger Madiun. Group A consisted of students who joined or got the teaching and learning process in constructing narrative text using series of pictures and group B consisted of students who did not get it. Based on this, the problem in the study was formulated in general as: was there significant difference on the students' achievement between the students who got the teaching and learning process using series of pictures in constructing narrative text and those who did not?. The students who got the teaching and learning process using series of pictures in constructing narrative text had better achievements than those who did not. There were two instruments used to collect the data; a set of an assessment/a test, and an achievement test called formative test. The formative test consisted of three competences; Task Achievement, Lexical Resource, Coherence and Cohesion. After collecting the data and grouping the sample, the writer computed the mean of the two groups and compared them by using the t - test. The t-test was used to see the differences in the students' achievements. The t-test resulted in a conclusion that there was a significant difference between group A and group B. The mean of group A was 7.85, the mean of group B was 7.05, and the computation of t was 9.43. The t probability was between two correlated group on the 0.5 level of significant for one tailed or directional test with the degree of freedom 50 was 1.684. Therefore the null hypothesis was rejected, and finally this research came with the answer to the problem that the teaching and learning process in constructing narrative text using series of pictures during a relatively short period of time had any affect with the English achievement of the third grade students of junior high level. The amount of time for the instruction and meeting was sufficient to gain a meaningful effect. Advisors: 1. Agus Wijayanto, Ph.D 2. Dra. Siti Zuhriyah Ariatmi, M.Hum